Jejunal Amyloidoma - a rare cause of gastrointestinal bleeding - Oyasiji, Tolutope (BioMed Central, 2009)
We report a case of localized amyloid tumor of the jejunum which presented with abdominal pain and gastrointestinal bleeding. We reviewed the pathophysiologic process that precipitates bleeding in this rare tumor. We also examined the documented radiologic and endoscopic features of amyloidosis of the small bowel in the light of our reported case. All with a view to add to the growing evidence on this rare tumor which will facilitate accurate diagnosis and management.